Implementasi Strategi Pembelajaran Problem Based Learning Dalam Pembelajaran Siswa Sekolah Dasar - Zikri Gusnita; Nidaul Lathifah Suhelmi; Gusmaneli Gusmaneli (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Education at the elementary school level is an important foundation for students on their educational journey to the next stage. The quality of the educational process in middle and high schools depends on how learning in elementary schools is designed by teachers. Therefore, it is very important for teachers to apply learning methods that suit the characteristics of students and are able to improve students' critical and innovative thinking abilities, as well as help students in solving the problems they face. Ideal learning does not only transfer knowledge, but also foster critical thinking, innovative and problem solving skills. Thus, students are ready to face various challenges in the future. The problem based learning (PBL) learning strategy or what is known as problem based learning can help students think more critically in understanding learning. Students will be grouped and asked to analyze a problem in depth, then conclude. This will create students' critical thinking skills that are in line with the abilities of elementary school level students